ANALISIS PERBANDINGAN PARAMETER ANTENA ARRAY 2x1 MIKROSTRIP PATCH BINTANG 24 DAN BINTANG 27 SERTA PERBANDINGAN KINERJA PADA MODEM CPE ROUTER LTE - Pradipa Arinal Haq Joewono; Muhammad Fauzan Edy Purnomo; Dwi Fadila Kurniawan (Jurnal Mahasiswa TEUB, 2023)
This study describes the methods and discussion for analysing the comparison of the two types of antennas, namely the 24-star patch and 27-star patch array 2x1 microstrip antennas which are then also compared through performance comparisons on LTE router CPE modem. The 27-star patch has a better value in measurement results than the 24-star patch antenna and in the simulation results and performance results, the two types of antennas have various values. In the simulation results, the best parameter values for Return loss, VSWR, and Bandwidth are in the 24-star patch, but for Gain and Directivity are in the 27-star patch. In the results of the performance comparison, the values of the two antenna variations are identical and fluctuate which can be caused by the influence of the modem connection with the access network. Keywords: Microstrip Antennas, Antenna parameters, Array technique, Implementation, CPE Router LTE Modem